2022
DOI: 10.3389/fevo.2021.779825
|View full text |Cite
|
Sign up to set email alerts
|

Welcome to the Dark Side: Partial Nighttime Illumination Affects Night-and Daytime Foraging Behavior of a Small Mammal

Abstract: Differences in natural light conditions caused by changes in moonlight are known to affect perceived predation risk in many nocturnal prey species. As artificial light at night (ALAN) is steadily increasing in space and intensity, it has the potential to change movement and foraging behavior of many species as it might increase perceived predation risk and mask natural light cycles. We investigated if partial nighttime illumination leads to changes in foraging behavior during the night and the subsequent day i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The influence of natural and artificial light is an increasingly important topic in wildlife conservation and ecosystem functioning (Gaston et al 2017, Hirt et al 2023). Yet we still know too little about the implications of artificial light on the activity of mammals (Hoffmann et al 2022). The prevalence of lunar phobia in our study suggests there may be more losers than winners when illumination increases in tropical forests.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of natural and artificial light is an increasingly important topic in wildlife conservation and ecosystem functioning (Gaston et al 2017, Hirt et al 2023). Yet we still know too little about the implications of artificial light on the activity of mammals (Hoffmann et al 2022). The prevalence of lunar phobia in our study suggests there may be more losers than winners when illumination increases in tropical forests.…”
Section: Discussionmentioning
confidence: 99%
“…Light pollution has been shown to have widespread effects on movement behaviours across several spatial scales, such as migration [19][20][21] and dispersal [22,23], as well as local movements within and between habitats [24][25][26][27]. These effects can be diverse [8]; for instance, at local scales there is evidence of reduced [28][29][30][31] as well as increased movement activity [32] in response to ALAN, which may be induced by the elevated risk or facilitation of predation, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial nightlight is a significant environmental cue that might affect these perceived trade‐offs. Numerous studies have shown that artificial nightlight can influence wildlife behaviors and movements, for example, by impacting their foraging and hunting strategies (Bennie et al, 2015; Ditmer, Stoner, Francis, et al, 2021; Hoffmann et al, 2022; Shier et al, 2020), movement and migration paths (Bliss‐Ketchum et al, 2016; Cabrera‐Cruz et al, 2018), vigilance behaviors (Yorzinski et al, 2015), physiological stress levels (Bedrosian et al, 2011; Ouyang et al, 2017), and energy budgeting (Touzot et al, 2019). Both increasing and ubiquitous, artificial nightlight emanates from sky glow, headlights, streetlamps, homes, and businesses and disturbs natural light regimes worldwide (Gaston, 2018; Gaston et al, 2014; Kyba et al, 2017; Sánchez de Miguel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%